Correlates of Empowerment of Ethnic Farmwomen in Assam - Roy, Deepjyoti; Ray, M N; Bora, Leema; Hussain, J; Payeng, Sadananda; Johari, Monosri; Jamatia, Keshab (Indian Journal of Extension Education, 2024)
An evaluation was conducted among the ethnic livestock and poultry farm women of Goalpara district of Assam to assess the impact of their socio-economic and psychological characteristics in relation to women’s empowerment in the years 2021–22. The respondents were selected via snowball sampling method, and their responses were recorded using a pre-tested interview schedule. The data indicated that factors such as social participation, age, years of livestock farming experience, contact with extension services, annual income from livestock rearing, attitudes towards scientific livestock farming, and time spent in livestock activities showed highly significant and positive correlations, while family size showed a highly significant and negative correlation with women empowerment.
Keywords: Farm women; Ethnic; Livestock rearing; Socio-economic; Social participation; Time spent; Women empowerment